Aqueous phase nitric oxide detection by an amine-decorated metal–organic framework. Issue 28 (6th March 2015) - Desai, Aamod V.; Samanta, Partha; Manna, Biplab; Ghosh, Sujit K.
Abstract : Selective and sensitive aqueous phase nitric oxide (NO) detection by ligand modulation in an amine-functionalized metal–organic framework has been demonstrated. Abstract : Selective and sensitive aqueous phase nitric oxide (NO) detection has been demonstrated by implementing an unsophisticated approach of ligand modulation in a porous, robust metal–organic framework (MOF). The detection is achieved through deamination by NO in an amine-decorated luminescent MOF. This is the first report of employing a physiologically stable, functionalized MOF as a NO sensor.